Multiple Force Platform Analysis of the Canine Trot: a New Approach to Assessing Basic Characteristics of Locomotion - Bertram, J. E. A.; Lee, D. V.; Todhunter, R. J.; Foels, Wendy S.; Jo Williams, Alma; Lust, G. (Veterinary and Comparative Orthopaedics and Traumatology, 1997)
Multiple platforms measure forces on different limbs simultaneously and provide a convenient means of determining locomotion parameters directly from force data. Four force platforms in series were used to measure force and positional data from simultaneous foot contacts of trotting dogs. Proper evaluation of fore and hindlimb forces from a complete stride requires a minimum of four platforms. Stride period, stride length, average velocity during the stride, relative phases of footfalls and duty factors can be determined directly from the force record. Impulse, average force and change in forward velocity can be determined by integrating the summed force/time curves over one stride period. These analytical techniques are illustrated using multiple platform data. Multiple platform analysis provides a comprehensive view of canine locomotion that cannot be achieved with a single platform.A multiple force platform system designed to analyze ground reaction forces of quadrupedal animals is described. This system provides all force and positional data required for the description of each footfall in a full trotting stride. Methods for calculating key locomotion parameters from multiple platforms are reported and their relevance to gait analysis is discussed.
Keywords: Locomotion; gait analysis; kineticals; canine